2019
DOI: 10.1111/jace.16600
|View full text |Cite
|
Sign up to set email alerts
|

Structures and pyroelectric properties for [111]‐oriented Mn‐doped rhombohedral 0.36PIN‐0.36PMN‐0.28PT crystal

Abstract: The crystal structures, pyroelectric properties, and thermal stability of [111]‐oriented 0.5 mol% Mn‐doped 0.36Pb(In1/2Nb1/2)O3‐0.36Pb(Mg1/3Nb2/3)O3‐0.28PbTiO3 (Mn‐0.36PIN‐0.36PMN‐0.28PT) ternary single crystal were investigated. The temperature dependence of the Raman spectra and dielectric properties revealed that the crystal exhibited a rhombohedral (R) structure at room temperature, and ferroelectric R → tetragonal (T) and ferroelectric T to paraelectric cubic (C) phase transitions at 130 and 175°C respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 22 publications
(53 reference statements)
1
25
0
Order By: Relevance
“…13,14 This led to the development a series of relaxor ferroelectric materials with high Curie temperature such as Pb(Yb 1/2 Nb 1/2 )O 3 -PbTiO 3 (PYNT) and BiScO 3 -PbTiO 3 (BSPT). [15][16][17][18][19][20][21][22] Among them, ternary relaxor ferroelectric single crystal, Pb(In 1/2 Nb 1/2 )O 3 -Pb(Mg 1/3 Nb 2/3 ) O 3 -PbTiO 3 (PIMNT), attracted much attention with rhombohedral to tetragonal phase transition temperature T R-T > 100°C and Curie temperature T C > 180°C and simultaneously demonstrated extremely high piezoelectric performance (d 33 up to 2800 pC/N). 19 Furthermore, previous works indicated that through Mn ion doping the domain motion could be further suppressed to reduce the conductivity and loss.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…13,14 This led to the development a series of relaxor ferroelectric materials with high Curie temperature such as Pb(Yb 1/2 Nb 1/2 )O 3 -PbTiO 3 (PYNT) and BiScO 3 -PbTiO 3 (BSPT). [15][16][17][18][19][20][21][22] Among them, ternary relaxor ferroelectric single crystal, Pb(In 1/2 Nb 1/2 )O 3 -Pb(Mg 1/3 Nb 2/3 ) O 3 -PbTiO 3 (PIMNT), attracted much attention with rhombohedral to tetragonal phase transition temperature T R-T > 100°C and Curie temperature T C > 180°C and simultaneously demonstrated extremely high piezoelectric performance (d 33 up to 2800 pC/N). 19 Furthermore, previous works indicated that through Mn ion doping the domain motion could be further suppressed to reduce the conductivity and loss.…”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, previous works indicated that through Mn ion doping the domain motion could be further suppressed to reduce the conductivity and loss. 21,22 Compared with bulk single crystals and ceramics, limited researches have been studied in PIMNT thin films. The growth and characterization of the ternary PIMNT thin film is at an early stage, and quite weak ferroelectric polarization was achieved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mn-doping has been used not only for modulation of the dielectric, ferroelectric, and piezoelectric 15,[18][19][20][21][22] energy storage properties 23) but also for improving the pyroelectric 24) and multicaloric effects. 25,26) Moreover, the effects of MnO 2 content on the permeability and electrical resistance of porous alumina-based ceramics have also been reported.…”
Section: Introductionmentioning
confidence: 99%